Exploring the Contribution of Violin Room to the Creative Industry and Music Culture in the Digital Age - Septian Okky Pradana; Irfanda Rizki Harmono Sejati; Isatou Jarju (Program Studi Pendidikan Musik FBS UNP, 2025)
Objective: This study aims to examine the contribution of Violin Room to the creative industry and music culture in the digital era. Method: This research employs a qualitative descriptive approach with a phenomenological design, allowing for an in-depth understanding of the experiences and practices implemented by Violin Room. Results and Discussion:The findings reveal that Violin Room adopts a systematic strategy in content creation, including planning, production, and publication stages. The content produced covers educational material such as violin tutorials and music theory, as well as entertainment, including student performances and cover songs. The promotional strategies employed involve SEO optimization, the use of attractive thumbnails, and active audience engagement through comments. Conclusion: Violin Room successfully utilizes the violin as a medium for creative content through structured production processes, engaging educational and entertaining content, and effective digital promotion. This not only bridges classical music traditions with digital culture but also broadens the appreciation of the violin in the modern era, contributing to the development of music-based creative content.